Diarrhetic shellfish toxins in Tasmanian coastal waters : causative dinoflagellate organisms, dissolved toxins and shellfish depuration - Wallace, GM (2011)
The Diarrhetic Shellfish Toxins (DST), okadaic acid (OA) + dinophysistoxin-1 (DTX-1), were detected above the regulatory limit of 0.20 ˜í¬¿g/g of digestive gland (DG) in (non-commercial) blue mussels (Mytilus edulis) from Sullivans Cove, Tasmania. Pectenotoxin-2 (PTX-2), PTX-2 seco acids and 7-epi-PTX-2 SA were also detected in mussels. This was associated with the occurrence of the toxic dinoflagellates, Dinophysis acuminata and D. fortii, which were seasonally prevalent at high cell densities (up to 7,380 cells/L for D. acuminata, 500 cells/L for D. fortii). A high density of D. truncata (1,850 cells/L) did not result in increased DST levels in M. edulis at Parsons Bay, Tasmania, suggesting that this may be a non- or weakly toxic dinoflagellate. Subtle variations among Dinophysis morphotypes can pose problems for rapid and accurate identification. Tasmanian sequences of the D1-D3 region of the large subunit rDNA of D. fortii were indistinguishable from those of D. fortii from France and D. acuta from the North Atlantic, while Tasmanian D. acuminata was indistinguishable from European and New Zealand D. acuminata. Genetic sequencing of New Zealand D. acuta failed to discriminate between Tasmanian D. fortii and New Zealand D. acuta and neither did sequencing discriminate between European D. fortii and D. acuta. A field depuration experiment was conducted in the Derwent River by placing M. edulis in 38 ˜í¬¿m mesh size cages to screen out Dinophysis plankton cells. Mussels displayed biphasic depuration kinetics with a faster rate of PTX loss over the first 30 days followed by an increase of OA + DTX-1 depuration once there was no further change in PTX levels. The slow rate of depuration of OA + DTX-1 from day 15 to 30 followed by an increase in depuration may be attributed to mussels using lipid storage during a period of reduced food availability leading to a release of toxins in bound fractions. Solid Phase Adsorption Toxin Tracking (SPATT) detected dissolved DST in the Derwent River seawater medium at levels as ...